Cephalic index and horizontal point of maximum width in children with normal brain development in China - Qinchuan Liang; Zhipeng Shen; Shouqin Sun; Jie Gong; Nan Bao (BMC, 2024)
Abstract Background To identify the normal range and distribution in the cephalic index(CI) and horizontal point of maximum width(H-PMW) of Chinese children with normal brain development. Methods We retrospectively analyzed Chinese Han children who visited our hospitals between June 2015 and June 2020 because of headache or suspected head injuries. 456 children (257 males, 199 females; aged 0-15 years) were enrolled and divided into 7 groups by age. The values of CI and H-PMW were measured using thin-slice brain computed tomography images. Results The overall mean CI was 86.6 ± 5.2. The mean CI for males was 87.0 ± 5.1, and that for females was 86.0 ± 5.2. The overall mean H-PMW was 53.7 ± 2.4. The mean H-PMW for males was 53.8 ± 2.5, and that for females was 53.5 ± 2.3. The averages CI reached the maximum (89.98) at the age of 4-6 months, then began to decrease, decreased to the minimum (84.31) at the age of 2-3 years, and then gradually increased, and reached 86.17 at the age of 8-15 years. The average H-PMW was the smallest (52.17) at the age of 4-6 months, and reached 54.88 at the age of 8-15 years. Conclusion The CI and H-PMW values of Chinese normal children reported in this study will provide a valuable reference to diagnose cranial deformities, assess the severity of the disease and the effectiveness of the treatment.